Functional verbs in Gungbe: the case of inherent complement verbs - Aboh, Enoch O. (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
Traditional linguistics assumes that verbs are lexical categories that typically merge in the predicate domain of a sentence: VP. This study shows that, in Gungbe (Kwa), a significantly large class of items functioning as verbs heading a VP in a sentence may also serve as functional elements that merge within the functional skeleton of the clause. The discussion builds on the analysis of Inherent Complement Verbs (ICVs). In the Kwa literature, ICVs are defined as verbs which require a complement in their citation form (e.g., dó wèzùn lit. plant race; ‘to run’). This paper argues that these verbs can first merge in two syntactic positions: little v and V. When merged in v, such verbs select for a VP-complement involving an abstract empty V which necessarily takes a bare NP as complement (Hale & Keyser 1993). When merged in V, however, these verbs pattern like other Gungbe lexical verbs in selecting a DP argument. The paper concludes that Gungbe, (and possibly Kwa languages in general) involve a class of verbal roots that can merge in the predicate head or in the functional domain. This finding supports Kayne’s (2009) recent antisymmetric approach to the lexicon.